Visietekst Steunpunt allochtone meisjes en vrouwen - Balli, Sultan; Ching Lin Pang; Rambaran, Sharmila; Vanpelt, Sofie; Perneel, Judith; Meerbergen, Aline (Steunpunt Allochtone Meisjes en Vrouwen, 2000)
"redactie: Balli Sultan, Ching Lin Pang, Rambaran Sharmila, Vanpelt Sofie ; eindredactie: Perneel Judith, Meerbergen Aline"